2013
DOI: 10.1007/s10692-013-9444-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation process of polyacrylonitrile fibers

Abstract: The effect of the content of active co-monomer, itaconic acid (IA), in PAN fiber on the thermal chemical transformations of the fiber during oxidation was studied. It was shown that the temperature for the start of the exotherm decreased as the IA content increased to 1. 8-1.9% and remained constant at 182°C as the content was increased further. A study of the effect of the degree of oxidation on the change of thermochemical characteristics of PAN fiber found that two successive exothermic processes occurred.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The cyano functionalities react to the complex structure of carbonyl groups and aromatic rings due to oxidative pretreatment (Scheme S1, ESI †). 59,[79][80][81][82][83][84][85][86][87][88][89][90] Compared to pristine PAN, quantitative elemental analysis (Table S2, ESI †) shows decreased contents of carbon, hydrogen and nitrogen in combination with an increased content of other elements, like oxygen.…”
Section: Base-catalysed Twin Polymerisation On Polyacrylonitrile Part...mentioning
confidence: 99%
“…The cyano functionalities react to the complex structure of carbonyl groups and aromatic rings due to oxidative pretreatment (Scheme S1, ESI †). 59,[79][80][81][82][83][84][85][86][87][88][89][90] Compared to pristine PAN, quantitative elemental analysis (Table S2, ESI †) shows decreased contents of carbon, hydrogen and nitrogen in combination with an increased content of other elements, like oxygen.…”
Section: Base-catalysed Twin Polymerisation On Polyacrylonitrile Part...mentioning
confidence: 99%
“…It was reported that the initial temperature (T i ) of the exothermic process decreased with increase in IA content to 1.8-1.9%, which also decreased the cyclization degree and increased the oxidation degree. 10,11 Moreover, the distribution of comonomer in the polymer chain can affect the stabilization reactions. The PAN-co-IA chains with regular and block architecture show more prominent cyclization and oxygen-uptake capabilities compared with randomly structured chains.…”
Section: Introductionmentioning
confidence: 99%
“…GelMA contains polar molecules such as NH 2 , COOH, and OH groups and acts as a charge carrier [26]. CNF NPs produced from PAN, due to thermal oxidation and carbonization processes, exhibit a polyconjugated system with mobile π-electrons [30]. Hence, when CNF NPs are blended with GelMA, the net polarized moieties present in the constructs increase, which is inferred from the steepness of the Nyquist admittance curves.…”
Section: Micrographs and Spectral Characteristicsmentioning
confidence: 99%